From an offender-based to an offense-based justice: Changes in sentencing patterns in the juvenile justice system in São Paulo from 1990 to 2006 - Oliveira, Thiago R. (Crime, law and social change, 2023)
Juvenile justice systems around the globe are becoming increasingly more similar to criminal justice systems. In Brazil, previous legislations focused on the individuals themselves and did not distinguish between young offenders and children in precarious conditions, but a new legislation in 1990 marked a rupture and introduced elements of criminal law. We leverage a unique data set representative of every adolescent who has been through the juvenile justice system in the state of São Paulo between 1990 and 2006 and provide a quantitative assessment of the changes in sentencing patterns in the period. Results suggest that judges increasingly prioritise violent and drug-related offenses when convicting adolescent defendants, indicating that the Brazilian juvenile justice system progressively resembles the criminal justice rationale by emphasising the ideal of proportionality between crime and punishment. We conclude with a discussion on pendular justice, suggesting that juvenile justice in Brazil is moving from a positivist-inspired to a classic-inspire justice system.